Benefits of umbilical cord milking versus delayed cord clamping on neonatal outcomes in preterm infants: A systematic review and meta-analysis - 齋藤 誠; Nagano Nobuhiko; Saito Makoto; Sugiura Takahiro; Miyahara Fumiko; Namba Fumihiko; Ota Erika (PLOS ONE, 2018)
Background\nOptimum timing of umbilical cord clamping has not been established in preterm infants.\nObjectives\nWe compared the short- and long-term effects of umbilical cord milking (UCM) versus delayed cord clamping (DCC) on infants born at less than 37 weeks of gestation.\nSearch methods\nA systematic review and meta-analysis was conducted according to the "Preferred Reporting Items for Systematic Reviews and Meta-Analyses" statement. We searched CINAHL, CENTRAL, EMBASE, MEDLINE, PubMed and ClinicalTrials.gov for relevant randomized controlled trials (RCTs).\nSelection criteria\nWe included individual and clustered RCTs comparing UCM to DCC for infants born before 37 weeks of gestation.\nData collection and analysis\nFour reviewers independently assessed trial quality and eligibility for inclusion.\nMain results\nTwo trials (255 preterm infants, 23 0/7 to 32 6/7 weeks of gestation) were included in the analysis. UCM was associated with fewer intraventricular hemorrhages (IVHs) (two trials, 255 infants; relative risk [RR] 0.45, 95% confidence interval [CI] 0.20 to 0.98, low quality of evidence) and UCM was an increased proportion of infants with a Bayley score at 2 years of age (two trials, 174 infants; Cognitive: RR 1.14, 95% CI 1.03 to 1.26, Language: RR 1.24, 95% CI 1.03 to 1.49, low quality of evidence) compared to DCC.\nConclusions\nUCM wasn't reduced in-hospital mortality and need for transfusion compared to DCC. But our study suggests that UCM may lower the risk of IVH and improve certain neurodevelopmental outcomes compared to DCC in preterm infants.